Membangun Kehidupan Toleransi Beragama dalam Komunitas Pelayanan Dialog Antaragama St. Ignasius Loyola dalam wilayah Paroki Kepanjen, Malang - Effendi, Yulius Rustan (Faculty of Cultural Sciences, Universitas Gadjah Mada, 2023)
Empowerment of awareness and the meaning of life of religious tolerance is a very important activity to be given to the community. The aim is to develop broad insights and understanding, to form tolerant behavior that is shown through concrete actions that support the creation of a safe, peaceful, harmonious life in an integrative society based on multiculturalism values. This tolerant life empowerment activity is a real effort to overcome various forms of conflict due to intolerance in society. Therefore, it is necessary to carry out community empowerment activities in the community of inter-religious dialogue services to build awareness of living as a tolerant nation and state. The method used in this community service activity is the socialization of empowerment (lectures) and simulations (dialogue/fraternal sharing and real action) guided by the speakers. The subjects in this empowerment activity are the people who join the Inter-religious Dialogue Service Community, especially the Inter-religious Dialogue Service Community of St. Ignasius Loyola in the Kepanjen Parish area, Malang, with a total of 80 participants. This activity was carried out for six (6) months, from May to October 2022. As a result of this empowerment of religious tolerance, the community has broad knowledge and understanding regarding the importance of a safe and harmonious life, and is able to build an open and adaptive culture of religious tolerance. === Kegiatan pemberdayaan kesadaran dan pemaknaan kehidupan toleransi beragama merupakan kegiatan yang sangat penting untuk diberikan kepada umat/masyarakat. Tujuannya adalah mengembangkan wawasan pengetahuan dan pemahaman yang luas, membentuk perilaku yang toleran yang ditunjukkan melalui aksi nyata yang mendukung terciptanya kehidupan yang aman, damai, dan harmonis dalam masyarakat yang integratif berbasis nilai-nilai multikulturalisme. Kegiatan pemberdayaan kehidupan yang toleran ini merupakan upaya nyata untuk mengatasi berbagai bentuk konflik akibat sikap intoleransi di masyarakat. Karena itu, perlu dilakukan kegiatan pemberdayaan masyarakat dalam komunitas pelayanan dialog antaragama untuk membangun kesadaran hidup berbangsa dan bernegara yang toleran. Metode yang digunakan dalam kegiatan pengabdian ini adalah sosialisasi pemberdayaan (ceramah) dan simulasi (dialog/ sharing persaudaraan dan aksi nyata) yang dipandu oleh pemateri. Subjek dalam kegiatan pemberdayaan ini adalah masyarakat yang bergabung dalam Komunitas Pelayanan Dialog Antaragama, khususnya Komunitas Pelayanan Dialog Antaragama St. Ignasius Loyola dalam wilayah Paroki Kepanjen, Malang yang berjumlah 80 peserta. Kegiatan ini dilaksanakan selama enam bulan, yaitu pada bulan Mei sampai Oktober 2022. Hasil kegiatan pemberdayaan hidup.